The Use of Jigsaw II to Teach Reading to STMIK Students - Susanti, Susanti (Universitas Pendidikan Indonesia, 2018)
ABSTRACT: The aims of this research are to encourage the students of class 2C1, Study Program of Informatic Technique at STMIK (Sekolah Tinggi Manajemen Informatika dan Komputer or College of Computer and Informatical Management) Pontianak, West Kalimantan, Indonesia engaged and assisted in learning English, especially for reading skill in the classroom. A CAR (Classroom Action Research) is the research design implemented to solve their reading problems encountered in classroom, such as the grammar, vocabulary, graphology, and the content. Action research is a teacher professional to the optimal achievement of the students to the lesson in teaching learning process in the classroom. And Jigsaw II is the technique applied in classroom activity, which students as the learning centered. Observation, tests, and documentary studys become the source of data collection technique used. The data collection obtained can be the qualitative and quantitative data of this study. This research found out that Jigsaw II technique applied is useful and effective not only for students’ achievement, but also for their involvement toward learning, especially teaching and learning reading skill to second semester students at the Sudy Program of Informatic Technique STMIK Pontianak, West Kalimantan, Indonesia.KEY WORD: Jigsaw II Technique; Cooperative Learning; Reading; Classroom Action Research; Students’ Achievement. ABSTRAKSI: “Penggunaan Teknik Jigsaw II dalam Pengajaran Membaca pada Mahasiswa STMIK Pontianak”. Tujuan penelitian adalah untuk memotivasi mahasiswa kelas 2C1, Program Studi Teknik Informatika di STMIK (Sekolah Tinggi Manajemen Informatika dan Komputer) Pontianak, Kalimantan Barat, Indonesia terlibat dan terbantu dalam belajar bahasa Inggris, terutama untuk keterampilan membaca di dalam kelas. PTK (Penelitian Tindakan Kelas) adalah model penelitian yang diterapkan untuk menyelesaikan masalah membaca yang ditemukan di kelas, seperti tata bahasa, kosa kata, model penulisan, dan isi teks. Penelitian tindakan adalah keprofessionalan guru untuk mengoptimalkan pencapaian keterampilan membaca mahasiswa dalam materi pembahasan pada proses belajar-mengajar di kelas. Dan Jigsaw II adalah teknik yang diterapkan dalam aktivitas kelas, di mana mahasiswa sebagai pusat pembelajaran. Pengamatan, tes, dan studi dokumentasi adalah teknik pengambilan data yang digunakan. Data yang terkumpul bisa berupa kualitatif dan kuantitatif data dalam studi ini. Penelitian ini menemukan bahwa teknik Jigsaw II yang diterapkan, ianya berguna dan efektif tidak hanya pada pencapaian, tetapi juga untuk keterlibatan mahasiswa semester 2 di Program Studi Teknik Informatika STMIK Pontianak, Kalimantan Barat, Indonesia dalam belajar, terutama dalam pengajaran keterampilan membaca dalam proses belajar-mengajar.KATA KUNCI: Teknik Jigsaw II; Pembelajaran Kooperatif; Membaca; Penelitian Tindakan Kelas; Pencapaian Mahasiswa.About the Author: Susanti, M.Pd. is a Lecturer at the Study Program of Information System STMIK (Sekolah Tinggi Manajemen Informatika dan Komputer or College of Computer and Informatical Management) Pontianak, Jalan Merdeka No.372 Pontianak City, West Kalimantan, Indonesia. Corresponding author is: santy.mayfoura@gmail.comSuggested Citation: Susanti. (2018). “The Use of Jigsaw II to Teach Reading to STMIK Students” in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 3(1), September, pp.85-96. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (January 19, 2018); Revised (February 20, 2018); and Published (March 30, 2018).